Antioxidant Properties of Ergosterol and Its Role in Yeast Resistance to Oxidation - Sebastien Dupont; Paul Fleurat-Lessard; Richtier Gonçalves Cruz; Céline Lafarge; Cédric Grangeteau; Fairouz Yahou; Patricia Gerbeau-Pissot; Odonírio Abrahão Júnior; Patrick Gervais; Françoise Simon-Plas; Philippe Cayot; Laurent Beney (MDPI AG, 2021)
Although the functions and structural roles of sterols have been the subject of numerous studies, the reasons for the diversity of sterols in the different eukaryotic kingdoms remain unclear. It is thought that the specificity of sterols is linked to unidentified supplementary functions that could enable organisms to be better adapted to their environment. Ergosterol is accumulated by late branching fungi that encounter oxidative perturbations in their interfacial habitats. Here, we investigated the antioxidant properties of ergosterol using in vivo, in vitro, and in silico approaches. The results showed that ergosterol is involved in yeast resistance to tert-butyl hydroperoxide and protects lipids against oxidation in liposomes. A computational study based on quantum chemistry revealed that this protection could be related to its antioxidant properties operating through an electron transfer followed by a proton transfer mechanism. This study demonstrates the antioxidant role of ergosterol and proposes knowledge elements to explain the specific accumulation of this sterol in late branching fungi. Ergosterol, as a natural antioxidant molecule, could also play a role in the incompletely understood beneficial effects of some mushrooms on health.